ANALISIS KOMPARASI MANAJEMEN LABA, PROFITABILITAS, DAN NILAI PERUSAHAAN SEBELUM DAN SESUDAH IMPLEMENTASI PSAK 69 - A. Hajar Nur Fachmi; Dewi Ayu Puspita; Whedy Prasetyo (Universitas Jember, 2020)
PSAK 69 is the accounting standard resulting from IFRS adoption related to agricultural activities that is effective as of January 1, 2018. This study aims to examine and analyze differences in earnings management, profitability, and value of firm before and after the implementation of PSAK 69. The population of this study is agricultural companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2018 period. The sample selection technique uses a purposive sampling method and the sample that meets the criteria is 17 companies with 34 observational data. The type of data in this study is secondary data. This type of research is quantitative research with a comparative approach. Hypothesis testing in this study using paired sample t-test. The results of this study indicate that there are differences in earnings management before and after the implementation of PSAK 69, while for profitability which is proxied by Return On Assets (ROA) and firm value there is no difference before and after the implementation of PSAK 69.Keywords: earnings management, profitability, PSAK 69, value of firm.